Language and Persuasion: Human Dignity at the European Court of Human Rights - Veronika Fikfak; Lora Izvorova (University of Hamburg, Institute of Law and Economics (ILE), 2022)
Although the concept of human dignity is absent from the text of the European Convention on Human Rights, it is mentioned in more than 2100 judgments of the European Court of Human Rights. The judges at the Court have used dignity to develop the scope of Convention rights, but also to signal to respondent states just how serious a violation is and to nudge them towards better compliance. However, these strategies reach dead ends when the Court is faced with government submissions that are based on a conception of dignity that is different from the notion of human dignity relied on by the Court. Through empirical analysis and by focusing on Russia, the country against which the term dignity is used most frequently, the paper maps out situations of conceptual contestation and overlap. We reveal how the Court strategically uses mirroring, substitutes dignity for other Convention values, or altogether avoids confrontation. In such situations, the Court's use (and non-use) of dignity becomes less about persuading states to comply with the Convention and more about preserving its authority and managing its relationship with states.
Keywords: 340